Incredible animals - Kallen, Stuart A., 1955- (Edina, Minn. : Abdo & Daughters ; Minneapolis, Minn. : Distributed by Rockbottom Books, 1991)
Presents record setters in the animal world, including the largest mammal, fastest animal, and most expensive pet.
Keywords: Animals -- Miscellanea -- Juvenile literature; Pets -- Miscellanea -- Juvenile literature; World records -- Juvenile literature; Animals -- Miscellanea; Pets -- Miscellanea; World records